The Moral Fiber of Life, Death and Resurrection in the Light of Islam: Lesson for Nigerian Youth - Usman Jimoh Muhammad (Pakistan Journal of Islamic Research)
The youthful stage of human life is considered in the paper as being paramount in the history of man. To this effect, this stage of life from the Islamic perspective is given crucial attention in a bid to ensure its judicious utilisation so as to achieve a fulfilled life, attain a memorable end and guarantee a pleasurable reward on the day of resurrection. The paper looks into the concept of youth, quantitative analysis of the Nigerian youth and some kinds of misconducts prevalence among them. Such misconducts examined are promiscuity, lust for vanity, cupidity and lack of respect for law and order. The paper avows that dereliction of parental upbringing, poverty and unemployment, glorification of corruption as against its condemnation and lackadaisical attitude of man to the concept of hereafter are among the key factors responsible for the glitches. While proposing a way out to the anomalies, the paper upholds that the youth must always checkmate their heart as it soundness paves way for emanation of good thoughts, noble utterances and laudable acts. The consciousness of the youth is further reawakened in the paper to the fact that at every point in time, man is tested by the devil attached to him. It reiterates that man subservient to the devil results into engrossment in all the aforementioned diabolic acts. However realisation of the concept of life as a test and its ephemeral nature, coupled with the concept of reward and punishment the paper asserts, are lessons for the Nigerian youth to make meaningful use of the sole opportunity of life and death which are precious to man. The paper recommends that parents should try to live up to expectation in the discharge of their duties to their children. In addition, the government and the well-to-do people in the society should rise up to the clarion call to free the nation from the scourge of poverty. This gesture would assist greatly in averting crimes and restoring peace and normalcy to the society.